2002
DOI: 10.1097/00007435-200204000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Neisseria gonorrhoeae and Chlamydia trachomatis at Entertainment Venues Among Men Who Have Sex with Men

Abstract: C trachomatis is a potentially significant pathogen in this population of urban homosexual men. Screening programs such as these are valuable as health-promotion exercises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Urethral infection prevalence ranged from 1.0% [86] to 5.0% [84]. Estimates for pharyngeal infection were low, ranging from 0.0% in both clinical and SOPV settings [80,82,90] to 2.7% [85]. A large well-conducted cohort study found the prevalence of rectal and urethral chlamydia at the time of recruitment to be higher among HIV-positive compared with HIV-negative men (5.9% versus 4.4% and 0.9% versus 2.2%), although this was not statistically significant [87,88].…”
Section: Resultsmentioning
confidence: 99%
“…Urethral infection prevalence ranged from 1.0% [86] to 5.0% [84]. Estimates for pharyngeal infection were low, ranging from 0.0% in both clinical and SOPV settings [80,82,90] to 2.7% [85]. A large well-conducted cohort study found the prevalence of rectal and urethral chlamydia at the time of recruitment to be higher among HIV-positive compared with HIV-negative men (5.9% versus 4.4% and 0.9% versus 2.2%), although this was not statistically significant [87,88].…”
Section: Resultsmentioning
confidence: 99%
“…1 Improved detection methods of Ct in urine allow community based testing in both sexes, including home based testing, 2-10 school based screening, 11 12 and tailored community outreach testing. [13][14][15][16][17][18][19][20][21] In a home based Ct screening project targeting 25-29 year olds, we found non-Dutch ethnicity, particularly Surinamese/ Antillean origin, a predictor for infection. 9 22 Participation in screening was less in people of non-Dutch ethnicity than of Dutch ethnicity (31% versus 42%, p,0.001).…”
mentioning
confidence: 76%
“…5 There was a co-infection of GU with chlamydia, similar study was also shown by Saleem et al and Nayak et al 4,5 Debattista et al also mentioned association with gonococci and chlamydia. 6 Hakenberg et al showed that, chlamydia infection was the cause of 25-50% male urethritis. 7 In our study 57 patients did not give history of use of condom.…”
Section: Discussionmentioning
confidence: 99%